Cetuximab or nimotuzumab plus intensity‐modulated radiotherapy versus cisplatin plus intensity‐modulated radiotherapy for stage II‐IVb nasopharyngeal carcinoma. Issue 6 (23rd June 2017) - You, Rui; Sun, Rui; Hua, Yi‐Jun; Li, Chao‐Feng; Li, Ji‐Bin; Zou, Xiong; Yang, Qi; Liu, You‐Ping; Zhang, Yi‐Nuan; Yu, Tao; Cao, Jing‐Yu; Zhang, Meng‐Xia; et al.
Abstract : To compare intensity‐modulated radiotherapy (IMRT) with cisplatin (CDDP) versus cetuximab (CTX) and nimotuzumab (NTZ) for Stage II‐IVb Nasopharyngeal Carcinoma (NPC). A total of 1, 837 patients with stage II –IVb NPC who received IMRT plus CTX or NTZ, or CDDP between January 2009 and December 2013 were included in the current analysis. Using propensity scores to adjust for potential prognostic factors, a well‐balanced cohort of 715 patients was created by matching each patient who underwent IMRT plus concomitant NTZ/CTX with four patients who underwent IMRT plus concomitant CDDP (1:4). Efficacy and safety were compared between the CTX/NTZ and CDDP groups of this well‐balanced cohort. Furthermore, we conducted multivariate analysis and subgroup analysis based on all the 1, 837 eligible cases. There was no significant difference between CTX/NTZ group and CDDP group in terms of DFS (3‐year, 86.7% vs . 86.2%, p  > 0.05), LRRFS (96.2% vs . 96.3%, p  > 0.05), DMFS (91.1% vs . 92.3%, p  > 0.05) and OS (91.7% vs . 91.9%, p  > 0.05). Subgroup analysis demonstrated a significant interaction effect between patients with IMRT plus CTX/NTZ and N3 node stage on LRRFS with the highest risk of loco‐regional relapse (HR 8.85, p  = 0.001). Significantly increased hematologic toxicities, gastrointestinal reactions were observed in the CDDP group ( p  < 0.05). Patients of 3.4 –4.7% experienced severe hematologic toxicities during the treatment with concomitant CTX and NTZ. Increased rate of CTX related‐skin reaction and mucositis was observed in the CTX group. CTX/NTZ used concurrently with IMRT may be comparable to those of the standard CDDP‐IMRT combination for maximizing survival for patients with stage II‐IVb NPC. Abstract : What's new? Standard treatment for nasopharyngeal carcinoma (NPC) that has spread to lymph nodes in the head and neck entails concurrent cisplatin (CDDP) and intensity‐modulated radiotherapy (IMRT). High toxicity rates, however, limit the utility of this approach. The present study examines an alternative strategy: cetuximab (CTX) and nimotuzumab (NTZ) plus IMRT. No differences in risk of disease progression, relapse, metastasis or death were observed in a direct comparison between CDDP plus IMRT and CTX/NTZ plus IMRT in NPC patients. Both regimens were associated with hematologic toxicities and with toxicities targeting different tissues, warranting further investigation of side effects specific to CTX/NTZ.